The electroconductivity of the liquid alloys of transition metals - Shvets, V.T.; Savenko, S.V.; Datsko, S.V. (Condensed Matter Physics, 2004)
The concentration dependance of electroresistivity of the liquid binary alloys
of transition metals Fe, Co and Ni is calculated. We considered the
contribution to conductivity from the s-electrons, described within the model
of nearly free electrons. The role of the partially occupied d-bands is
reduced to resonance scattering of the s-electrons on d-states. The interaction
of the s- and d-electrons is described by the hybridization potential
of s- and d-states. The interaction with the ions, not including the partially
occupied d-states, is described using the pseudopotential of the electronion
interaction. The electroresistivity of the alloys is calculated in the second
order of the perturbation theory in pseudopotential and hybridization
potential. The concentration dependance of electroresistivity of the binary
alloys approaches the linear regime as the resonance scattering of the
s-electrons on d-states prevails over the scattering on the ions. The calculations
exhibit good agreement with the experimental data. Розрахована концентраційна залежність електроопору бінарних сплавів рідких перехідних металів Fe, Co, Ni. Електронами провідності вважаються лише s-електрони, що описуються в моделі майже вільних електронів. Роль d-електронів частково заповненої d-оболонки зводиться до резонансного розсіяння s-електронів на d-станах. Взаємодія s-електронів з іонною підсистемою, що не містить частково заповнених d-станів, описується псевдопотенціалом електрон-іонної взаємодії. Взаємодія s- та d- електронів описується потенціалом гібридизації s- і d-станів. Електроопір сплавів розраховується у другому порядку теорії збурень за псевдопотенціалом та потенціалом гібридизації. Концентраційна залежність електроопору бінарних сплавів рідких перехідних металів тим ближча до лінійної, чим більше резонансне розсіяння s-електронів на d-станах перевищує їх розсіяння на іонній підсистемі. Результати чисельних розрахунків знаходяться у добрій відповідності з експериментальними даними.